Relationships among factual and perceived knowledge of harms of waterpipe tobacco, perceived risk, and desire to quit among college users. (December 2014) - Lipkus, Isaac M; Eissenberg, Thomas; Schwartz-Bloom, Rochelle D; Prokhorov, Alexander V; Levy, Janet
Waterpipe tobacco smoking is increasing in the United States among college students. Through a web-based survey, we explored associations among factual and perceived knowledge, perceived risks and worry about harm and addiction, and desire to quit among 316 college waterpipe tobacco smoking users. Overall, factual knowledge of the harm of waterpipe tobacco smoking was poor, factual and perceived knowledge was weakly correlated, both forms of knowledge were related inconsistently to perceived risks and worry, and neither form of knowledge was associated with the desire to quit. Findings provide preliminary insights as to why knowledge gaps may not predict cessation among waterpipe users.